Item Analysis of an English Summative Test: A Classical Test Theory Approach in Indonesian Junior High School Context - Rahmawaty Ahmad; Rasuna Rasid Talib; Magvirah El Walidayni Kau (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Assessment plays a crucial role in evaluating students’ learning outcomes; however, the quality of summative test instruments often remains questionable due to the limited use of systematic evaluation procedures. This study aims to examine the quality of English summative test items administered to eighth-grade students at SMP Negeri 1 Suwawa Timur using Classical Test Theory (CTT). A descriptive quantitative design was employed, analyzing 40 multiple-choice items completed by 56 students using Anates V4 software. The analysis focused on item validity, difficulty level, discriminating power, and distractor effectiveness. The results revealed that only 55% of the items were valid, while 45% were invalid. Most items (62.5%) were of moderate difficulty, yet no easy items were identified, indicating an imbalance. Furthermore, a substantial proportion of items demonstrated weak discriminating power, and several distractors were ineffective. These findings suggest that although some test items meet acceptable standards, a considerable number require revision. This study highlights the importance of systematic item analysis in improving the validity, reliability, and overall quality of assessment instruments.